Geopolitics Beyond Recognition: Somaliland, Israel, and the Changing Meaning of Statehood - Rizama , Zhizhi Meshach (Universitas Muhammadiyah Makassar, 2026)
The evolving relationship between Somaliland and Israel raises urgent questions about how diplomacy beyond formal recognition is reshaping the politics of sovereignty and legitimacy in Africa, particularly in a region governed by strong territorial norms. This study aims to examine the political implications of emerging ties between a non-recognized polity and an established state, and to analyze how recognition operates as a strategic and political instrument rather than a purely legal act. Employing a qualitative case study design, the research relies on official statements, diplomatic communiqués, policy documents, and responses from regional organizations, which are analyzed using thematic analysis and qualitative discourse analysis to trace competing narratives of legitimacy and strategic framing. The findings show that three distinct legitimacy logics structure the interaction: performance-based legitimacy articulated by Somaliland through references to governance, stability, and elections; strategic-security legitimacy advanced by Israel through concerns over maritime security, counterterrorism, and regional influence; and normative-legal legitimacy emphasized by Somalia and regional organizations through the defense of territorial integrity and inherited borders. The study concludes that diplomacy without formal recognition is becoming an increasingly viable modality of geopolitical engagement in the Horn of Africa. The novelty of this research lies in conceptualizing recognition as a layered and contested process that links de facto statehood to regional security logics and norm entrepreneurship. The article contributes to scholarship on unrecognized states and African sovereignty norms while offering policy-relevant insights for regional organizations and external partners engaged in the evolving politics of statehood in the Horn of Africa.